Rekontekstualisasi Konsep Ketuhanan Abd Samad al-Palimbani - Rijal, Syamsul; Umiarso, Umiarso (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2018)
The discourse about God has not been limitedly discussed merely within philosophical and theological dimensions but it has been also discussed within tasawuf approach. A number of Muslim thinkers have so far discussed their understanding of God from this point of view. Abd Samad al-Palimbani was one of the prominent Muslim scholars who tried to discuss the issue of divinity from tasawuf perspective. Al-Palimbani, himself, was a Muslim thinker of 18th century who possessed a specific thought about divinity within such dimension. The approach he employed has become a particularly exceptional matter in the study of divinity in the field. The very basic concept of his thought about God can be observed, among other, within his a monumentally master-piece, entitled Sayr al-S?lik?n. This article seeks to reveal the discourse of divinity discussed in Al-Palimbani?s book. It has been argued that through the concept of martabat tujuh (seven grades), promulgated by Al-Palimbani in his Sayr al-S?lik?n, a s?lik (a seeker of God) will be able to understand and recognize God who possesses W?jib al-Wuj?d as one His attributes. Al-Palimbani?s concept of martabat tujuh undoubtedly puts him as a central figure within the discussion of God and divinity from tasawuf dimension.